An Overview of Using Steel Fibers in Reinforced Concrete Structural Elements to Improve Shear Reinforcement - Baarimah, A. O.; Sharifah Maszura, Syed Mohsin (Universiti Malaysia Pahang, 2016)
Recently, several studies have been conducted to investigate the shear behaviour of steel fiber reinforced concrete (SFRC). Over the last few decades, steel fibers have been shown to be applicable and effective in improving the shear reinforcement. This paper presents a summary of the main findings from the primary research contributors. Besides discussion on the research efforts, recommendations for the future research in using steel fibers to improve shear reinforcement are provided. This paper conclude that using steel fibers in reinforced concrete slab can possibly reduce the thickness of slab and fibers has substantial effect to serve as part of shear reinforcement in reinforced concrete slab.